1966
DOI: 10.1063/1.1727297
|View full text |Cite
|
Sign up to set email alerts
|

Anion—Cation Interactions in Molten Inorganic Nitrates: Vibrational Analysis

Abstract: An assessment of the spectral data (solid state, solutions, and molten state) for LiNO3, NaNO3, KNO3, RbNO3, CsNO3, AgNO3, and TlNO3 reveals significant features not in harmony with the selection rules for NO3− ions of D3h point-group symmetry. Correlations with lower symmetries show that the selection rules for the Point Groups C2v and Cs are adequate for the observed spectra. A ``contact'' ion-pair model is advanced for nearest-neighbor pairwise association in which the metal ion interacts with the oxygen at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

1967
1967
2009
2009

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(14 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…This order is in accord with the order of increasing force constant for the metal-oxygen stretch in molten nitrates [17], Cs+< Rb+< K+< Li+< Na + [B], but disagrees with the order of increasing polarizing power of cations defined as (cation charge)/(cation radius), Cs + < Rb + < K + < Na + < Li + [C], which is the same as that noted for the extent of anion-cation interaction from N.M.R. studies of a series of chlorides [17].…”
Section: Mean-square Torquesupporting
confidence: 79%
“…This order is in accord with the order of increasing force constant for the metal-oxygen stretch in molten nitrates [17], Cs+< Rb+< K+< Li+< Na + [B], but disagrees with the order of increasing polarizing power of cations defined as (cation charge)/(cation radius), Cs + < Rb + < K + < Na + < Li + [C], which is the same as that noted for the extent of anion-cation interaction from N.M.R. studies of a series of chlorides [17].…”
Section: Mean-square Torquesupporting
confidence: 79%
“…the 740 cm-' band observed in the infrared spectrum. Surprisingly, however, the separation of the components of v3(E1) decreases slightly as the concentration increases and no splitting is reported for the molten salt (27). The explanation may lie in the symmetry of the ion atmosphere surrounding the nitrate ion.…”
Section: + ( a D + No3 -( A Dmentioning
confidence: 72%
“…Raman bands at 1439, 1358, 1067, and 726 cm-' have been interpreted in terms of a contact ion pair in the melt with C,, or C, symmetry (27). The increasing separation of components of v3(E1) with increasing concentration has already been noted for aqueous solutions of LiNO, (see Fig.…”
Section: + ( a D + No3 -( A Dmentioning
confidence: 94%
“…The silver atoms are above the nitrate plane, off the C3-axis. It has even been suggested that silver ions are found in molten salt (27) in the same locations as they are in concentrated aqueous solutions (5 1).…”
Section: Introductionmentioning
confidence: 99%